2005
DOI: 10.1111/j.1600-0765.2005.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

The up‐regulation of heme oxygenase‐1 expression in human gingival fibroblasts stimulated with nicotine

Abstract: Taken together, these results suggest that HO-1 expression is significantly up-regulated in gingival tissues from cigarette smokers, and nicotine may, among other constituents, be responsible for the enhanced HO-1 expression in vivo. The regulation of HO-1 expression induced by nicotine is critically dependent on the intracellular GSH concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 35 publications
9
35
0
Order By: Relevance
“…As shown in Fig. 1, HO-1 expression is generally low in normal oral mucosa and is exclusively limited to actively differentiating basal cells, which is similar to the results reported by CHANG et al 2 . In the present study, HO-1 positive cells were mainly found in basal and parabasal cells of the dysplastic epithelium and in cancerous cells.…”
Section: Discussionsupporting
confidence: 88%
“…As shown in Fig. 1, HO-1 expression is generally low in normal oral mucosa and is exclusively limited to actively differentiating basal cells, which is similar to the results reported by CHANG et al 2 . In the present study, HO-1 positive cells were mainly found in basal and parabasal cells of the dysplastic epithelium and in cancerous cells.…”
Section: Discussionsupporting
confidence: 88%
“…Although previous studies reported that nicotine causes injury to periodontal ligament cells via multiple mechanisms, including c-Fos, COX-2, heme oxygenase-1 and oxidative stress [22][23][24] , the molecular mechanisms of these effects have not been fully elucidated. Elevated P.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of activation in this case is proposed to be through reduced hepatocyte production of reactive oxygen species and subsequent reduction in cellular oxidative stress (48), mechanisms of cell damage that may be activated by ricin. Nicotine's effect on antioxidant systems is complex, with reports of decreased activities of antioxidant enzymes such as glutathione peroxidase and catalase, but nicotine has also been shown to upregulate expression of heme oxygenase-1, a stress-inducible protein that functions as an antioxidant enzyme (49), as well as superoxide dismutase levels in the kidney (50). With ricin having significant prooxidant effects (26,30,51), any protective antioxidant enzymes that may be induced by nicotine may prove effective in maintaining organ function following ricin exposure.…”
Section: Discussionmentioning
confidence: 99%